You light up my life! - Okpoluaefe Godspower Udezi, Suruthimitra Okpoluaefe; Parameswaran, Kavesha; Baharin, Hanif; Othman, Siti Sarah; Saad, Wan Zuhainis (Universiti Putra Malaysia Press, 2017)
It is often misconstrued that communication can only be done by macro-organisms including the common man. This is the central dogma that is circulated universally. Organisms like Alivibrio fischeri, or what was once known as Vibrio fischeri has challenged this theory. Microorganisms are able to communicate through a mechanism called quorum sensing.